Independent Predictors of Heat-Related Illness-Induced Acute Respiratory Failure: A Multicenter Cross-sectional Study - Kuo, Wan-Yin; Huang, Chien-Cheng; Hsu, Chien-Chin; Lin, Hung-Jung; Su, Shih-Bin; Liu, Chung-Feng; Sung, Mei-I; Chen, Chi-An; Guo, How-Ran (Archives of Academic Emergency Medicine, 2025)
Introduction: Acute respiratory failure (ARF) is a critical complication of heat-related illness (HRI). This study aimed to identify predictors of HRI-induced ARF in patients presenting to the emergency department (ED). Methods: Patients aged 20 years and above diagnosed with HRI (ICD-9-CM code 992 or ICD-10 code T67) who visited the EDs of the three hospitals in Tainan, Taiwan between January 2010 and October 2021, were included. Demographic characteristics, comorbidities, and laboratory data were collected. Logistic regression models using the backward elimination method were constructed to identify the independent predictors of HRI-induced ARF. Results: 820 patients with the mean age of 50.0 ± 18.4 years were studied (80.0% male). 29 (3.5%) cases experienced ARF. Patients with ARF were less likely to walk on arrival compared to those without it (27.6% vs. 61.8%, p < 0.001). Additionally, they had higher prevalence of Glasgow Coma Scale (GCS) scores ≤ 8 (p = 0.003), respiratory rate > 20 breaths/min (p < 0.001), body temperature ≥ 40°C (p < 0.001), hypertension (p = 0.001), cerebrovascular disease (p = 0.001), and chronic obstructive pulmonary disease (p = 0.042). The multivariable logistic regression revealed that body temperature ≥ 40 °C on arrival (odds ratio (OR): 7.76; 95% confidence interval (CI): 3.14–19.15), an initial respiratory rate > 20 breaths/min (OR: 8.19; 95% CI: 3.48–19.24), and history of hypertension (OR: 3.38; 95% CI: 1.52–7.52) were predictors of HRI-induced ARF. Conclusions: Elevated body temperature, respiratory rate, and a history of hypertension were key predictors of ARF in HRI patients, aiding in patient stratification for emergency care.